2018
DOI: 10.1016/j.srhc.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Access and utilisation of reproductive, maternal, neonatal and child health services among women who inject drugs in coastal Kenya: Findings from a qualitative study

Abstract: Highlights Globally there is limited research concerning women who inject drugs. This paper reports important insights related to the experiences, needs and barriers preventing the utilisation of reproductive maternal, neonatal and child health services among women who inject drugs in coastal Kenya. Findings from this study will inform the development of equitable, comprehensive, and family-centered RMNCH interventions targeting women who inject drugs, including the integration of RMNCH services within harm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 42 publications
0
29
0
2
Order By: Relevance
“…The characteristics of the study sample is summarized in Table 1, and is reported in more detail elsewhere (Ayon et al, 2017, Mburu et al, 2018b, Ndimbii et al, 2018. In brief, the average age of the 45 women was 28.5 (range 19 -56) years (Mburu et al, 2018b).…”
Section: Primary Study Samplementioning
confidence: 99%
“…The characteristics of the study sample is summarized in Table 1, and is reported in more detail elsewhere (Ayon et al, 2017, Mburu et al, 2018b, Ndimbii et al, 2018. In brief, the average age of the 45 women was 28.5 (range 19 -56) years (Mburu et al, 2018b).…”
Section: Primary Study Samplementioning
confidence: 99%
“…In addition, IDIs and FGDs were audio-recorded and lasted between 45 and 60 min. Additional details regarding the primary data collection and analysis have been reported in a series of several primary manuscripts [16,[25][26][27].…”
Section: Aims Setting and Methodology Of Primary Data Collectionmentioning
confidence: 99%
“…This paper reports information generated through a secondary analysis of pre-existing qualitative data. The primary study [25,26] was a qualitative study conducted in 2015 with aim of exploring the needs, barrier, and determinants of sexual and reproductive health (SRH) of women who inject drugs in the Kenyan coastal towns of Mombasa and Kilifi.…”
Section: Primary Study Aims and Designmentioning
confidence: 99%
See 2 more Smart Citations